Marine low-temperature concrete additive and preparation method thereof
By using scientific proportions of raw materials such as silane/polymer hybrid modified silica and anti-freeze fibers in marine low-temperature concrete, the problem of cracks and increased porosity in cold zone concrete is solved, which is significantly It improves the frost resistance and mechanical properties of concrete and extends the service life of the structure.
Patent Information
- Application Number
- CN202411571735.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Concrete in cold zones is prone to cracks and increased porosity during freeze-thaw cycles, affecting structural safety and durability. The existing marine concrete admixtures are mainly concentrated in corrosion resistance and fail to effectively improve frost resistance.
The raw materials such as silane/polymer hybrid modified silica, anti-freeze fiber, gas-induced water reducer, silica fume, sodium hexametaphosphate and calcium chloride were prepared through silanization modification and PEI grafting. A marine low-temperature concrete additive was developed to significantly improve the frost resistance and mechanical properties of concrete.
Effectively reduce the porosity inside concrete, inhibit crack growth, improve frost resistance and mechanical properties, and extend the service life of concrete structures.
Smart Images

Figure BDA0005120629200000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete admixtures, and in particular relates to a marine low-temperature concrete additive and a preparation method thereof. Background Art
[0002] The temperature difference between day and night in cold regions is large, and the freeze-thaw cycle (seasonal freeze-thaw and day and night freeze-thaw) will cause damage to the multiphase media of water, ice, and aggregate in concrete, making the internal pore changes of concrete complex. When freeze-thaw cycles occur, the capillary walls inside the concrete will be affected by expansion pressure and osmotic pressure. When the pressure exceeds the ultimate tensile strength of the concrete, cracks will occur and continue to expand, and then form through cracks, affecting the safety of concrete structures and engineering operations in cold regions. The addition of external materials can effectively inhibit the growth and development of concrete cracks, reduce the porosity inside the concrete, and improve the frost resistance of the concrete.
[0003] How to improve the freezing damage and performance enhancement technology of hydraulic concrete in freeze-thaw environment has important practical significance for improving the durability of hydraulic concrete in cold regions, and provides important technical support for the construction, operation and maintenance of concrete structures in cold-region water conservancy projects. However, most of the current research on marine concrete admixtures focuses on corrosion resistance. For example, Chinese patent CN 107892502A discloses a marine concrete anti-corrosion admixture, which mainly involves improving the impermeability and chloride ion corrosion resistance of marine concrete and enhancing the corrosion resistance of marine concrete. Chinese patent CN 114634325A discloses an anti-corrosion, anti-cracking and permeability-reducing agent for marine concrete and its preparation method. This invention can effectively resist the corrosion of chloride ions and sulfates, improve the density of concrete, increase the compressive and flexural strength of concrete, and extend the service life. Therefore, it is urgent to develop a marine low-temperature concrete additive to improve the comprehensive performance of concrete, especially the freeze-thaw resistance. Summary of the invention
[0004] The present invention aims at the problems existing in the prior art and provides a marine low-temperature concrete additive, which can effectively reduce the porosity inside the concrete, improve the frost resistance of the concrete, inhibit the growth and development of concrete cracks, and at the same time improve the mechanical properties of the concrete and extend the service life.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0006] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 5-15 parts of silane / polymer hybrid modified silicon dioxide, 5-9 parts of antifreeze fiber, 1-5 parts of air-entraining water-reducing agent, 0.5-3 parts of silica fume, 0.5-1 parts of sodium hexametaphosphate and 0.5-1 parts of calcium chloride.
[0007] Preferably, the preparation method of the silane / polymer hybrid modified silica is:
[0008] (1) Silanization modification:
[0009] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, and disperse it by ultrasonication for 30 min. Add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica.
[0010] (2) PEI grafting:
[0011] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0012] Preferably, the particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000, and the mass concentration of the aqueous solution is 50 wt%.
[0013] Preferably, the antifreeze fiber is formed by mixing polypropylene fiber, carbon fiber and PVA fiber in a mass ratio of 5:2:3.
[0014] Preferably, the air-entraining water-reducing agent is one or more of sodium lauryl sulfate, sodium lauryl polyether sulfate, and octadecyl dimethyl benzyl ammonium chloride.
[0015] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0016] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0017] All raw materials used in the present invention are commercially available.
[0018] The additive of the present invention can be directly added into marine concrete when used, and the addition amount is 0.5-5% of the cement amount in the concrete.
[0019] Beneficial Effects
[0020] First, a silane coupling agent containing epoxy groups, γ-glycidyloxypropyltrimethoxysilane, is selected to perform surface silanization treatment on silica. The methoxy group in γ-glycidyloxypropyltrimethoxysilane can react with the hydroxyl group on the surface of silica to form Si-O-Si bonding; and the epoxy group can serve as the active site for the subsequent grafting reaction. Then, a water-soluble polymer containing amino groups, such as polyethyleneimine (PEI), is selected to be grafted onto the surface of silica modified with γ-glycidyloxypropyltrimethoxysilane through a ring-opening reaction. The primary amine in PEI reacts with the epoxy group to form a chemical bond. After grafting PEI, a large number of amino groups are introduced onto the surface of silica, which can significantly improve its compatibility with the cement system. At the same time, the unreacted primary amine in PEI can also serve as a reaction site to chemically bond with hydration products in concrete, such as calcium silicate hydrate (CSH), thereby enhancing the interfacial bonding between silica and the cement matrix. In addition, the amino groups in PEI can also consume alkaline substances (such as calcium hydroxide) in the concrete pore fluid through acid-base neutralization reaction, reduce the pH value of the pore fluid, slow down the alkali-aggregate reaction, and improve the long-term durability of concrete. Therefore, on the one hand, the hybrid modified silica has enhanced interfacial bonding with the cement matrix, which can improve the integrity of the internal structure of the concrete and reduce the initiation of microcracks during the freeze-thaw cycle. In addition, the surface hydrophilicity of the hybrid modified silica is enhanced, which can improve its dispersibility, optimize the pore structure of the concrete, reduce the macroporosity, and thus reduce the risk of freeze-thaw damage; on the other hand, the hybrid modified silica can react chemically with the cement hydration product to form a dense interface transition zone, which improves the ability of the concrete to resist freeze-thaw erosion. In addition, PEI can also chelate calcium ions in the concrete through complexation, form a cross-linked network structure in the cement matrix, improve the strength and toughness of the concrete, and enhance the freeze-thaw resistance.
[0021] The present invention simultaneously adds antifreeze fibers composed of polypropylene fiber, carbon fiber and PVA fiber, wherein the polypropylene fiber can effectively inhibit the shrinkage cracks of concrete in the plastic and initial hardening stages, thereby improving the crack resistance of concrete; the addition of carbon fiber can effectively resist crack extension, enhance the deformation and damage mechanism of concrete, thereby improving its toughness; and the addition of PVA fiber, i.e. polyvinyl alcohol fiber, has a good improvement on the durability of concrete under extreme environments. PVA fiber itself has a certain air entraining effect, which prevents the invasion of external environmental ions and delays the corrosion and damage time of concrete structure. At the same time, PVA fiber has high elastic modulus and high strength, which can effectively control the cracks caused by factors such as plastic shrinkage and temperature change in concrete, prevent and inhibit the formation and development of cracks, and improve durability. When the three are used at the same time, the synergistic cooperation can effectively form a three-dimensional network structure, reduce the water migration in the freeze-thaw cycle process, thereby improving the antifreeze performance of concrete, effectively inhibiting the plastic shrinkage and shrinkage cracks of concrete, extending the service life of concrete structure, and improving overall durability.
[0022] Air-entraining water-reducing agent forms stable tiny bubbles in cement paste, which improves the frost resistance and workability of concrete. In addition, it can be adsorbed on the surface of cement particles, reducing surface tension and reducing water consumption.
[0023] Adding silica fume, which has a small particle size, can fill the pores in concrete, improve the density of concrete, reduce capillary pores, and thus improve the strength and durability of concrete. In addition, silica fume and other round fine particles have a "ball effect", which can reduce the friction resistance of concrete mixtures, improve the fluidity of concrete, and improve the workability of concrete.
[0024] In summary, the additive of the present invention significantly improves the freeze-thaw resistance, crack resistance and mechanical strength of concrete through the scientific ratio of hybrid modified silica and compound antifreeze fiber as well as air-entraining water-reducing agent and silica fume, thereby extending the service life of the concrete structure and improving the overall durability. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0026] Example 1
[0027] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 5 parts of silane / polymer hybrid modified silica, 5 parts of antifreeze fiber, 1 part of air-entraining water-reducing agent, 0.5 parts of silica fume, 0.5 parts of sodium hexametaphosphate, and 0.5 parts of calcium chloride.
[0028] The preparation method of the silane / polymer hybrid modified silicon dioxide is:
[0029] (1) Silanization modification:
[0030] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica;
[0031] (2) PEI grafting:
[0032] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0033] The particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000; and the mass concentration of the aqueous solution is 50 wt%.
[0034] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0035] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added while slowly stirring, and mixed evenly, and sodium hexametaphosphate and calcium chloride are continued to be added and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0036] The antifreeze fiber is formed by mixing polypropylene fiber, carbon fiber and PVA fiber in a mass ratio of 5:2:3.
[0037] The air-entraining water-reducing agent is sodium lauryl sulfate.
[0038] Example 2
[0039] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 10 parts of silane / polymer hybrid modified silicon dioxide, 7 parts of antifreeze fiber, 3 parts of air-entraining water-reducing agent, 2 parts of silica fume, 0.5 parts of sodium hexametaphosphate and 0.5 parts of calcium chloride.
[0040] The preparation method of the silane / polymer hybrid modified silicon dioxide is:
[0041] (1) Silanization modification:
[0042] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica;
[0043] (2) PEI grafting:
[0044] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0045] The particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000; and the mass concentration of the aqueous solution is 50 wt%.
[0046] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0047] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0048] The antifreeze fiber is formed by mixing polypropylene fiber, carbon fiber and PVA fiber in a mass ratio of 5:2:3.
[0049] The air-entraining and water-reducing agent is sodium lauryl polyether sulfate.
[0050] Example 3
[0051] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 15 parts of silane / polymer hybrid modified silicon dioxide, 9 parts of antifreeze fiber, 5 parts of air-entraining water-reducing agent, 3 parts of silica fume, 1 part of sodium hexametaphosphate and 1 part of calcium chloride.
[0052] The preparation method of the silane / polymer hybrid modified silicon dioxide is:
[0053] (1) Silanization modification:
[0054] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica;
[0055] (2) PEI grafting:
[0056] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0057] The particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000; and the mass concentration of the aqueous solution is 50 wt%.
[0058] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0059] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0060] The antifreeze fiber is formed by mixing polypropylene fiber, carbon fiber and PVA fiber in a mass ratio of 5:2:3.
[0061] The air-entraining water-reducing agent is octadecyl dimethyl benzyl ammonium chloride.
[0062] Comparative Example 1
[0063] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 15 parts of silicon dioxide, 9 parts of antifreeze fibers, 5 parts of air-entraining water-reducing agent, 3 parts of silica fume, 1 part of sodium hexametaphosphate, and 1 part of calcium chloride.
[0064] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0065] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0066] The antifreeze fiber is formed by mixing polypropylene fiber, carbon fiber and PVA fiber in a mass ratio of 5:2:3.
[0067] The air-entraining water-reducing agent is octadecyl dimethyl benzyl ammonium chloride.
[0068] The particle size of the silicon dioxide powder is 50-100 nm.
[0069] In this comparative example, except for directly using silicon dioxide powder, the other raw materials and preparation method are the same as those in Example 3.
[0070] Comparative Example 2
[0071] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 15 parts of silane / polymer hybrid modified silicon dioxide, 9 parts of antifreeze fiber, 5 parts of air-entraining water-reducing agent, 3 parts of silica fume, 1 part of sodium hexametaphosphate and 1 part of calcium chloride.
[0072] The preparation method of the silane / polymer hybrid modified silicon dioxide is:
[0073] (1) Silanization modification:
[0074] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica;
[0075] (2) PEI grafting:
[0076] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0077] The particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000; and the mass concentration of the aqueous solution is 50 wt%.
[0078] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0079] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0080] The antifreeze fiber is polypropylene fiber.
[0081] The air-entraining water-reducing agent is octadecyl dimethyl benzyl ammonium chloride.
[0082] In this comparative example, except that the antifreeze fiber only uses polypropylene fiber, the other raw materials and preparation methods are the same as those in Example 3.
[0083] Comparative Example 3
[0084] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 15 parts of silane / polymer hybrid modified silicon dioxide, 9 parts of antifreeze fiber, 5 parts of air-entraining water-reducing agent, 3 parts of silica fume, 1 part of sodium hexametaphosphate and 1 part of calcium chloride.
[0085] The preparation method of the silane / polymer hybrid modified silicon dioxide is:
[0086] (1) Silanization modification:
[0087] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica;
[0088] (2) PEI grafting:
[0089] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0090] The particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000; and the mass concentration of the aqueous solution is 50 wt%.
[0091] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0092] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0093] The antifreeze fiber is carbon fiber.
[0094] The air-entraining water-reducing agent is octadecyl dimethyl benzyl ammonium chloride.
[0095] In this comparative example, except that the antifreeze fiber only uses carbon fiber, the other raw materials and preparation methods are the same as those in Example 3.
[0096] Comparative Example 4
[0097] A marine low-temperature concrete additive comprises the following raw materials in parts by weight: 15 parts of silane / polymer hybrid modified silicon dioxide, 9 parts of antifreeze fiber, 5 parts of air-entraining water-reducing agent, 3 parts of silica fume, 1 part of sodium hexametaphosphate and 1 part of calcium chloride.
[0098] The preparation method of the silane / polymer hybrid modified silicon dioxide is:
[0099] (1) Silanization modification:
[0100] Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica;
[0101] (2) PEI grafting:
[0102] Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
[0103] The particle size of the silicon dioxide powder in step (1) is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000; and the mass concentration of the aqueous solution is 50 wt%.
[0104] A method for preparing a marine low-temperature concrete additive comprises the following steps:
[0105] The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, then the fiber is broken up in a mixer at a speed of 1000 rpm to make it evenly dispersed, deionized water is added to a stirring container, air entraining water reducer and silica fume are added under slow stirring, and mixed evenly, sodium hexametaphosphate and calcium chloride are continued to be added, and mixed evenly, and then silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that the components are fully dispersed; the mixture is transferred to a ball mill and ball-milled at a speed of 300 rpm for 2 hours to further homogenize the components, and finally the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50%.
[0106] The antifreeze fiber is PVA fiber.
[0107] The air-entraining water-reducing agent is octadecyl dimethyl benzyl ammonium chloride.
[0108] In this comparative example, except that only PVA fiber is used as the antifreeze fiber, the other raw materials and preparation methods are the same as those in Example 3.
[0109] Performance Testing
[0110] The concrete material ratio is shown in Table 1 below:
[0111] Table 1 Concrete mix ratio
[0112] Cement / kg Fly ash / kg Water / kg Sand / kg stone / kg 260 90 160 670 1060
[0113] Cracking test:
[0114] In a standard curing room, a cracking test was conducted on the test concrete (additives were added to the concrete according to 1% of cement mass) after 7 days of curing. Three samples were selected for synchronous testing to ensure the accuracy of the test data. The test results were the average values of the three groups of test values. The hydraulic concrete cracking test mold was made according to the length, width and height of 600mm×600mm×100mm, and the channel steel with a length, width and height of 600mm×600mm×100mm was used as the frame of the mold. The bottom plate and the four sides of the mold were fixed by bolts. Hydraulic concrete was poured in the mold to improve the rigidity of the mold, and the surface of the mold was smoothed with plastic film. After the hydraulic concrete specimen was formed, the plastic film was removed, and the surface of the specimen was dried with an electric fan. The cracking of the concrete was observed with a microscope of 0.01mm, and the cracking time, length, width and number of cracks were recorded. The total cracking area of the hydraulic concrete was observed for 24 hours from the pouring, and the data were recorded in Table 2.
[0115] Table 2 Concrete cracking test
[0116] <![CDATA[Number of cracks / (pieces / m 2 )]]> <![CDATA[Cracking area / (mm 2 / strip)]]> <![CDATA[Total cracking area / (mm 2 / m 2 )]]> Example 1 7 9.1 65 Example 2 6 7.2 46 Example 3 5 6.4 33 Comparative Example 1 17 13.6 241 Comparative Example 2 12 11.2 139 Comparative Example 3 12 10.3 126 Comparative Example 4 11 10.7 122
[0117] According to the cracking tests of Examples 1-3 and Comparative Examples 1-4, the number of cracks and the cracking area of Examples 1-3 using the additives of the present invention are much lower than those of Comparative Examples 1-4 without silane / polymer hybrid modified silica and compound antifreeze fibers. And the anti-cracking effect of Example 3 of the present invention is the best. On the one hand, the hybrid modified silica has enhanced interfacial bonding with the cement matrix, which can improve the integrity of the internal structure of the concrete and reduce the initiation of microcracks. On the other hand, the hybrid modified silica can react chemically with the cement hydration product to form a dense interface transition zone, thereby improving the ability of the concrete to resist freeze-thaw erosion. PEI can also chelate calcium ions in the concrete through complexation, form a cross-linked network structure in the cement matrix, improve the strength and toughness of the concrete, and enhance the anti-freeze-thaw performance. In addition, the compound fiber can be evenly distributed in the concrete to form a three-dimensional network structure, which effectively inhibits the plastic shrinkage and shrinkage cracks of the concrete.
[0118] Compressive strength test:
[0119] The additives of each embodiment and comparative example were mixed in a 1% (cement mass) amount and placed in concrete to make a 100mm×100mm×100mm cubic specimen. According to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the 7d and 28d compressive strengths of each specimen were tested, and the average strength of the three specimens in the same group was taken as the compressive strength of the concrete in this group. The test compressive strength data is shown in Table 3.
[0120] Table 3 Compressive strength
[0121] Group 7d compressive strength (MPa) 28d compressive strength (MPa) Example 1 31.7 51.8 Example 2 32.9 53.3 Example 3 35.6 55.1 Comparative Example 1 22.8 31.7 Comparative Example 2 27.4 42.5 Comparative Example 3 29.1 43.9 Comparative Example 4 28.7 43.4
[0122] According to the test data of the examples and comparative example 1 in the table, the compressive strength of the examples in which silane / polymer hybrid modified silica is added to the additive is much higher than that of comparative example 1, especially the difference between the 7d compressive strength of example 3 and that of comparative example 1 is more obvious, indicating that the concrete with the silane / polymer hybrid modified silica admixture has better early strength performance. And in terms of the compressive strength at 28d, the compressive strength of the examples is also much better than that of the comparative example.
[0123] Relative dynamic elastic modulus test:
[0124] The prepared concrete (additives are mixed into concrete at 1% of cement mass) was subjected to freeze-thaw cycle comparison test after standard curing for 28 days. The mass loss rate and relative dynamic elastic modulus of concrete were tested after 100 and 300 freeze-thaw cycles, referring to the quick freezing method in GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Table 4.
[0125] Table 4 Relative dynamic elastic modulus
[0126] Freeze-thaw 100 times Freeze-thaw 300 times Example 1 89 83 Example 2 93 88 Example 3 95 91 Comparative Example 1 62 54 Comparative Example 2 75 68 Comparative Example 3 77 71 Comparative Example 4 79 72
[0127] It can be seen from the relative elastic modulus results after 100 and 300 freeze-thaw cycles in Table 4 that the relative dynamic elastic modulus of the embodiment is significantly higher than that of the comparative example. Compared with 100 freeze-thaw cycles, the decreasing rate of the relative dynamic elastic modulus of the embodiment after 300 freeze-thaw cycles is better than that of the comparative example. The less the relative dynamic elastic modulus decreases, the fewer microcracks inside the concrete and the better the antifreeze performance. After 300 freeze-thaw cycles, the relative dynamic elastic modulus of the embodiment is still as high as 83%, from which it can be seen that the embodiment of the present invention can improve the antifreeze performance of concrete.
[0128] Mass loss rate and compressive strength loss rate test:
[0129] Each embodiment and comparative example was mixed into concrete at 1% of cement mass to prepare a 100mm×100mm×100mm cubic specimen. According to the slow freezing method of "GB / T 50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", each specimen was subjected to freeze-thaw treatment for 100 times and 300 times. After the freeze-thaw treatment, the mass loss rate (unit: %) and compressive strength loss rate (unit: %) of each specimen were detected and are shown in Table 5.
[0130] Table 5 Mass loss rate and compressive strength loss rate
[0131]
[0132] It can be seen from the data in the above table that after 100 freeze-thaw treatments, the mass loss rate and compressive strength loss rate of the embodiment are significantly lower than those of the comparative example. After 300 freeze-thaw treatments, the mass loss rate and compressive strength loss rate of the embodiment are still significantly lower than those of the comparative example. In particular, the result of Example 3 is significantly better than that of Comparative Example 1, indicating that the addition of silane / polymer hybrid modified silica and compound antifreeze fiber can significantly improve the frost resistance of concrete.
[0133] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A marine low-temperature concrete additive, characterized in that: The preparation method comprises the following raw materials in parts by weight: 5-15 parts of silane / polymer hybrid modified silicon dioxide, 5-9 parts of antifreeze fiber, 1-5 parts of air entraining water reducing agent, 0.5-3 parts of silica fume, 0.5-1 parts of sodium hexametaphosphate and 0.5-1 parts of calcium chloride.
2. The marine low-temperature concrete additive according to claim 1, characterized in that: The preparation method of the silane / polymer hybrid modified silicon dioxide is: (1) Silanization modification: Weigh 10 g of silica powder, add it to 100 mL of anhydrous ethanol, ultrasonically disperse it for 30 min, add 2 mL of γ-glycidyloxypropyltrimethoxysilane, react at 60 ° C for 6 h under nitrogen protection, filter, wash with ethanol 3 times, and vacuum dry at 60 ° C for 12 h to obtain silanized modified silica; (2) PEI grafting: Weigh 5 g of silanized modified silica, add it to 100 mL of deionized water, ultrasonically disperse it for 30 min, add 10 mL of polyethyleneimine aqueous solution, adjust the pH to 9, react at 80 ° C for 12 h under nitrogen protection, filter, wash with deionized water until neutral, and vacuum dry at 60 ° C for 24 h to obtain silane / polymer hybrid modified silica.
3. The marine low-temperature concrete additive according to claim 2, characterized in that: Step (1) The particle size of the silicon dioxide powder is 50-100 nm; the molecular weight of polyethyleneimine is 1000-3000, and the mass concentration of the polyethyleneimine aqueous solution is 50wt%.
4. The marine low-temperature concrete additive according to claim 1, characterized in that: The antifreeze fiber is formed by mixing polypropylene fiber, carbon fiber and PVA fiber in a mass ratio of 5:2:
3.
5. The marine low-temperature concrete additive according to claim 1, characterized in that: The air-entraining water-reducing agent is one or more of sodium lauryl sulfate, sodium lauryl polyether sulfate, and octadecyl dimethyl benzyl ammonium chloride.
6. A method for preparing the marine low-temperature concrete additive according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: The antifreeze fiber is dried at 60°C for 4 hours to remove surface moisture, and then the fiber is broken up in a mixer at a speed of 1000 revolutions per minute to make it evenly dispersed. Deionized water is added to a stirring container, and air entraining water reducer and silica ash are added under slow stirring and mixed evenly. Sodium hexametaphosphate and calcium chloride are continued to be added and mixed evenly. Then, silane / polymer hybrid modified silica and antifreeze fiber are slowly added to the stirring container, and stirring is continued for 20 minutes to ensure that all components are fully dispersed. The mixture is transferred to a ball mill and ball-milled at a speed of 300 revolutions per minute for 2 hours to further homogenize all components. Finally, the solid content of the mixture is tested, and deionized water is added to adjust the solid content to 40-50% to obtain the final product additive.
Citation Information
Patent Citations
Anticorrosive additive for marine concrete
CN107892502A
Anti-corrosion anti-cracking permeability reducing agent for marine concrete and preparation method of anti-corrosion anti-cracking permeability reducing agent
CN114634325A
Anti-cracking and anti-freezing concrete for waterproof protective layer of railway bridge deck
CN109928703A
Anti-freezing concrete and preparation method thereof
CN110218030A
Polyphenyl granule-aerogel composite cement-based thermal insulation material
CN113698151A
Cited By
Easily-demoulded texture bare concrete as well as preparation method and application thereof
CN120535261A
Easy-to-release textured plain concrete and its preparation method and application
CN120535261B
Internal admixture containing inorganic self-repairing material as well as preparation method and application of internal admixture
CN122167067A